Regenerative agriculture in Australia: the changing face of farming - Alexanderson, Mathew Stephen; Luke, Hanabeth; Lloyd, David John (Frontiers in Sustainable Food Systems, 2024)
The agricultural and social landscape of rural Australia is changing, with many farmers interested in, and some actively moving towards, regenerative agriculture—but what do we understand of the farmers undertaking these transitions? Regenerative agriculture is a holistic way of managing landscapes that aims to move beyond sustainability to regenerate natural systems, while supporting farming system viability. While several authors have discussed the higher-level philosophical underpinnings of regenerative agriculture, there are few empirical studies exploring the motivators for farmers to implement a suite of practices within the regenerative agriculture tool-kit. By undertaking an online survey targeting regenerative farmers, this study identifies common attributes of regenerative farmers, as well as key motivators for, and barriers to change, including perceived benefits arising from the approach. An online survey was promoted through the social media pages of three farming groups, resulting in 96 self-identifying Australian regenerative farmers included in this analysis. Results demonstrate that a clear and recent shift has taken place for this group, who may feel ostracized within their local community, hence often rely on information from online and international sources of agricultural information. This article builds a core understanding of the goals, attributes, aspirations and challenges of regenerative farmers and offers a definition of regenerative agriculture that is derived from farmer responses.